OPTIMIZING BPJS CLAIMS MANAGEMENT: AN ANALYSIS OF SUBMISSION ACCURACY, ADMINISTRATIVE PROCESS EFFICIENCY AND ITS IMPACT ON HOSPITAL FINANCIAL SUSTAINABILITY - Vip Paramarta; Deny Teguh Setyaji; Alexandra DeSousa Guterres (RADJA PUBLIKA, 2025)
The National Health Insurance (JKN) system managed by BPJS Kesehatan aims to ensure access to health services for the community. However, the implementation of this program faces challenges in hospital claims management, including delays in claims submission and payment. This study analyzes the accuracy of BPJS Health claims submission by hospitals, the factors that affect the efficiency of claims administration, and the impact on hospital financial sustainability. The method used in this research is a qualitative method because researchers want to see the natural conditions of the object. The results showed that delays in claims occurred due to a long administrative process, errors in filling out documents, and limited knowledge of medical personnel in diagnosis codification. In addition, the claims payment process took up to 3 months and 10 days, causing financial pressure for the hospital. To overcome these problems, good coordination between health workers and coders, increased accuracy in recording medical data, and utilization of information technology are needed to accelerate claims verification. With an improved claims management system, hospitals can maintain financial stability and improve the quality of health services.